On the use of climate models for estimating the non-stationary characteristic values of climatic actions in civil engineering practice - Abrahamczyk, Lars; Uzair, Aanis (Frontiers in Built Environment, 2023)
The characteristic values of climatic actions in current structural design codes are based on a specified probability of exceedance during the design working life of a structure. These values are traditionally determined from the past observation data under a stationary climate assumption. However, this assumption becomes invalid in the context of climate change, where the frequency and intensity of climatic extremes varies with respect to time. This paper presents a methodology to calculate the non-stationary characteristic values using state of the art climate model projections. The non-stationary characteristic values are calculated in compliance with the requirements of structural design codes by forming quasi-stationary windows of the entire bias-corrected climate model data. Three approaches for the calculation of non-stationarity characteristic values considering the design working life of a structure are compared and their consequences on exceedance probability are discussed.